Reducing treatment by means of physical rehabilitation after lower limb amputation - Liana Dugina (Kharkiv State Academy of Physical Culture, 2015)
Purpose: the main approaches to the assignment of physical rehabilitation restorative treatment after lower limb amputations. Material and Methods: theoretical analysis and synthesis of modern scientific and methodological literature data on methods of comprehensive rehabilitation after lower limb amputations. Results: the features of the application of physical rehabilitation after lower limb amputations, tasks and presents the main approaches to the appointment of medical physical training, therapeutic massage and physical therapy in preparation for prosthetics. Conclusions: demonstrated that therapeutic physical training, therapeutic massage and physical therapy are effective means of physical rehabilitation of patients after lower limb amputations.